Degree of coronary occlusions links to the patient clinical outcome: four cases of double culprits acute ST-segment elevation myocardial infarction - Ilham Uddin; Anindia Wardhani; Misbah Hari Cahyadi; Desy Ayu Puspitasari; Pipin Ardhianto; Udin Bahrudin; Yan Herry; Sodiqur Rifqi (Journal of Biomedicine and Translational Research, 2021)
Background: Double coronary culprit lesions in ST-segment elevation myocardial infarction (STEMI) is uncommon. Despite successful primary percutaneous coronary intervention (PPCI) in all culprit lesions, the clinical outcome remains unfavorable and the possible factors for the outcome are not fully understood.Cases Presentation: We reported four cases of double culprit lesions STEMI underwent PPCI. Patient A, a 62 y.o. male with extensive anterior-inferior STEMI, had total occlusion (TO) at both proximal left anterior descending (LAD) and mid right coronary artery (RCA). Patient B, a 42 y.o. male with extensive anterior-inferior STEMI, had subtotal occlusion (STO) at proximal RCA and TO at proximal LAD. Both of them had RBBB ECG pattern. Patient C, a 67 y.o. male with inferior STEMI had 90% thrombus occlusion at proximal–mid LAD and TO at proximal RCA. Patient D, a 65 y.o. male with anteroseptal STEMI, had STO at proximal LAD and 80% thrombus occlusion at mid left circumflex. The cardiomyocyte infarction biomarkers increased in all patients. Although all of them underwent successful PPCI in all of culprit lesions, they suffered from acute heart failure and two of them experienced recurrent ventricular arrhythmia episodes. One of them (patient A) died two days post PPCI. He was only patient who suffering from total occlusion in LAD and RCA with TIMI thrombus 5 and experienced a total atrioventricular block post-PPCI.Conclusion: STEMI with coronary double culprits have severe clinical outcome, regardless of the successful PCI. The degree of coronary occlusions might be linked to the patient clinical outcome.